Agriculture and poverty reduction in Ghana - Thurlow, James (Bill & Melinda Gates Foundation, 2018)
If you asked most Ghanaians where the opportunities of the future lie, they would point to Accra, Kumasi, and other big cities. The country’s thousands of small farms symbolize the past—and they symbolize poverty. But this dichotomy misses an important point. Agriculture is not going away; it is transforming. Subsistence farming may be gradually disappearing (the number of Ghanaians who say farming is their primary job fell from 57 to 44 percent between 2006 and 2016), but it is being replaced by a more dynamic, productive, market-oriented agriculture.